224k views
0 votes
Need help plz
5(x – 1) + 3x = 7(x + 1)

( 80 pts 4 answering right)

2 Answers

6 votes

Answer:

x = 12

Explanation:

5(x – 1) + 3x = 7(x + 1)

5x - 5 + 3x = 7x + 7

8x - 5 = 7x + 7

8x - 7x = 7 + 5

x = 12

User Andrii Startsev
by
6.4k points
1 vote

Answer:

x = 12

Explanation:

Let's use the distributive rule first for both 5(x - 1) and 7(x + 1). When using the distributive rule to expand parentheses, remember to find the sum of the product of the "outside number" with each of the "inside numbers".

5(x - 1): 5 is the outside number and both x and -1 are the inside numbers.

5 * x + 5 * (-1) = 5x - 5

7(x + 1): 7 is the outside number and both x and 1 are the inside numbers.

7 * x + 7 * 1 = 7x + 7

Now, we can put these back into the equation:

5x - 5 + 3x = 7x + 7

Combine all the x's and the constants:

8x - 5 = 7x + 7

x = 7 + 5 = 12

Thus, the answer is x = 12.

Hope this helps!

User Phani Kumar PV
by
6.9k points